Proposed Solutions for Improving Queue Management Efficiency at Bebeke Om Aris - Elvira Ananda, Chintya (Jurnal Pendidikan Indonesia, 2025)
The rapid growth of the food and beverage sector, especially in bustling urban environments, requires ongoing improvements in operational effectiveness to keep up with the rising demand and client standards. This study examines the queue management system at the Hasanudin branch of Bebeke Om Aris, a renowned restaurant in Bandung, Indonesia, that specializes in duck and chicken cuisine. The restaurant's operational performance is significantly impacted by extended waiting times experienced during busy periods. The objective of this research is to to develop and evaluate strategies for diminishing waiting times and enhancing overall efficiency through a quantitative methodology. This study was driven by the observed inefficiencies in the current queue management system, characterized by huge waits and longer waiting periods, especially on weekends. These inefficiencies not only impede the delivery of services but also provide a possible threat to the restaurant's competitive standing in the market. The main goal of this study is to determine and recommend effective strategies for optimizing queue management in order to achieve a maximum waiting time of 5 minutes during the busiest hours, as specified by the restaurant's management. During a four-week period, a structured observation method was used to collect primary data on customer arrivals, queue lengths, and waiting times. The observation notably targeted Saturday evenings, which are known for having the highest client inflow. The gathered data was subsequently employed to generate simulation models using Arena software, which assessed different scenarios, such as the integration of self-service kiosks, the adoption of QR code ordering systems, and the augmentation of cashier counters. The queuing theory was employed to examine these scenarios and assess important performance measures, including average waiting time, queue length, and system utilization rates. The investigation demonstrated that the integration of self-service kiosks and QR code ordering systems can effectively decrease waiting times and enhance operational efficiency. The self-service kiosks enable customers to autonomously place orders, thereby decreasing the burden on cashiers and expediting the ordering procedure. Similarly, the implementation of the QR code system simplifies the procedure by allowing customers to place orders and make payments directly from their smartphones, thereby reducing congestion at the cashier. The simulation results demonstrated a significant reduction in both mean waiting times and queue lengths, thereby successfully attaining the intended performance goals. This study's findings enhance the subject of operational management by showcasing how queuing theory and simulation tools may be practically applied to optimize service delivery in the food service industry. The suggested solutions give a scalable approach that can be customized for other comparable environments, providing a foundation for restaurants seeking to improve their service efficiency and customer satisfaction. Subsequent studies could investigate the enduring impacts of these interventions on customer behavior and business performance, as well as their suitability in various categories of food service enterprises